2021
DOI: 10.3390/molecules27010212
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of Extracellular Silver Nanoparticles from Streptomyces aizuneusis: Antimicrobial, Anti Larval, and Anticancer Activities

Abstract: The ability of microorganisms to reduce inorganic metals has launched an exciting eco-friendly approach towards developing green nanotechnology. Thus, the synthesis of metal nanoparticles through a biological approach is an important aspect of current nanotechnology. In this study, Streptomyces aizuneusis ATCC 14921 gave the small particle of silver nanoparticles (AgNPs) a size of 38.45 nm, with 1.342 optical density. AgNPs produced by Streptomyces aizuneusis were characterized by means of UV-VIS spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Although there have been many reports on the various biological activities of greenly synthesized AgNPs in the past, there has been little analysis of their constituents, so the anti-inflammatory mechanism of this kind of AgNPs is rarely studied. 22,23 In this study, we found that silver only accounted for a small part of the composition of AC-AgNPs (32.71 ± 4.87%), and other antiinflammatory substances accounted for the majority. Therefore, this explains why the AgNPs synthesized by chemical or physical methods have proinflammatory effects, while AC-AgNPs have anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although there have been many reports on the various biological activities of greenly synthesized AgNPs in the past, there has been little analysis of their constituents, so the anti-inflammatory mechanism of this kind of AgNPs is rarely studied. 22,23 In this study, we found that silver only accounted for a small part of the composition of AC-AgNPs (32.71 ± 4.87%), and other antiinflammatory substances accounted for the majority. Therefore, this explains why the AgNPs synthesized by chemical or physical methods have proinflammatory effects, while AC-AgNPs have anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 51%
“…From the chemical structure point of view, they all contain abundant hydroxyl groups and unsaturated bonds, so they are also adsorbed on the silver nanoparticles as reducing agents and stabilizers during the synthesis of AC-AgNps, endowing AC-AgNps with some specific biological activity. Although there have been many reports on the various biological activities of greenly synthesized AgNPs in the past, there has been little analysis of their constituents, so the anti-inflammatory mechanism of this kind of AgNPs is rarely studied. , In this study, we found that silver only accounted for a small part of the composition of AC-AgNPs (32.71 ± 4.87%), and other anti-inflammatory substances accounted for the majority. Therefore, this explains why the AgNPs synthesized by chemical or physical methods have proinflammatory effects, while AC-AgNPs have anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 58%
“…The cytotoxicity of green synthesized CMBNPs was determined by using a NRU colorimetric assay. This assay is based on the capacity of live cells to bind and integrate neutral red into lysosomes [ 29 ]. The cytotoxicity was measured as a concentration-dependent reduction in the uptake of neutral red in response to CMBNP exposure and serves as a sensitive indicator of both cell integrity and growth inhibition, determining IC 50 (50% inhibiting concentration).…”
Section: Resultsmentioning
confidence: 99%
“…The experiment was performed in triplicates, and the assay was read at 492 nm. The cytotoxicity (%) was evaluated using Equation (2) [12,13]:…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%